1988
DOI: 10.3109/01913128809032238
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic Crystalloid Structures in a Malignant Fibrous Histiocytoma: Ultrastructural and Cytochemical Study

Abstract: Crystalloid structures were frequently observed in the cytoplasm of the tumor cells of a malignant fibrous histiocytoma arising in the left leg of a 71-year-old female. These structures were located in the cytoplasm of the fibroblastlike and histiocyte-like tumor cells. The structures consisted of an aggregate of dense granules without unit membrane. Neither glycoproteins nor polysaccharides were detected in these structures on sections stained with chromic acid-phosphotungstic acid or periodic acid-thiocarboh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Since it has been reported that paramyxovirus protein is sensitive to RNase on acrylate embedded sections, our results are in agreement in indicating the presence of ribonucleic acid in the structures (Gyorkey et al 1972;Mii et al 1988). However, we cannot solve the problem of why the structures showed a positive immunocytochemical reaction to two antibodies, and why the reaction was positive in only one case.…”
Section: Discussionsupporting
confidence: 81%
“…Since it has been reported that paramyxovirus protein is sensitive to RNase on acrylate embedded sections, our results are in agreement in indicating the presence of ribonucleic acid in the structures (Gyorkey et al 1972;Mii et al 1988). However, we cannot solve the problem of why the structures showed a positive immunocytochemical reaction to two antibodies, and why the reaction was positive in only one case.…”
Section: Discussionsupporting
confidence: 81%
“…Other features seen in thecase of Mii et aI. 16 which are also seen in annulate lamellae are the apparent continuity of the lamellae (in some areas) with the rough endoplasmic reticulum and the presence of electron-dense bodies associated with the crystalloids. Dense bodies have been described in association with annulate lamellae and seem to represent nucleolar Differentiation of annulate lamellae appears to result in the dispersal of these dense cytoplasmic masses and the development of extensive rough endoplasmic reticulum and many polyribosomes.I8 This case report illustrates two interesting points: the hitherto undescribed presence of annulate lamellae in a malignant peripheral nerve sheath tumour and another example of a sarcoma with the histological features of pleomorphic MFH exhibiting ultrastructural evidence of Schwann cell differentiation.…”
Section: Discussionmentioning
confidence: 83%